A study on the genus Macroscytus Fieber, 1860 from China (Hemiptera: Heteroptera: Cydnidae) - Zhu, Geng-Ping; Liu, Guo-Qing; Lis, Jerzy A. (Zootaxa, 2010)
Eight species of the genus Macroscytus Fieber, 1860 are reported from China. Among these is M. vietnamicus J.A. Lis, 1991, recorded for the first time from the country; moreover, the occurrence of M. badius (Walker, 1867) in its southern parts (Hainan Province) is confirmed. A key to the Chinese species of the genus is provided, along with habitus figures and illustrations of hind legs and the male genitalia. A phenomenon of instability in the cephalic chaetotaxy of M. aequalis (Walker, 1867), M. badius, M. popovi J.A. Lis, 1991, and M. vietnamicus J.A. Lis, 1994, are briefly discussed.